2013
DOI: 10.1111/ggi.12155
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of certified need of care in the long‐term care insurance system and its risk factors in the elderly of Japanese population‐based cohorts: The ROAD study

Abstract: Both underweight and obesity, as well as low muscle strength and physical ability, are risk factors for certification of need of care. Considering muscle dysfunction is a risk factor for occurrence, screened individuals are recommended to receive early intervention programs regardless of muscle volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 22 publications
(34 reference statements)
1
52
0
5
Order By: Relevance
“…Physical performance measures did not differ significantly between low and medium BMI groups for either sex. Many previous studies have found that higher BMI is associated with poor performance [13,14,16,17,19,[23][24][25], and our present study results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Physical performance measures did not differ significantly between low and medium BMI groups for either sex. Many previous studies have found that higher BMI is associated with poor performance [13,14,16,17,19,[23][24][25], and our present study results were consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Marsh et al [23] reported an association between low HGS and an increased risk of developing major mobility disability, as well as a U-shape relationship between baseline BMI and the risk of developing major mobility disability. Akune et al [24] reported that both underweight and obese individuals were at an increased risk for need of care and decreased muscle strength and physical ability. The association between BMI and frailty also shows a U-shaped relationship, in which the level of frailty in elderly individuals increases among those with low and high BMIs [25].…”
Section: Introductionmentioning
confidence: 99%
“…The main texts of the remaining 521 papers were checked, and a further 488 papers that did not meet the selection criteria were excluded. Thirty-three papers and 97 sets of data [5, that met the selection criteria were ultimately subject to analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Hand grip strength is also used in elderly adults as a screening index for sarcopenia, which is defined as a decline in skeletal muscle mass and muscle function [1,2]. Furthermore, poor hand grip strength is associated with mortality [3,4] and disability [4,5] in older adults and has been found to be a useful index for frailty [6,7]. Reports have also emerged in recent years demonstrating a relationship between hand grip strength and oxidative DNA damage, which has been found to be related to cancer, heart disease, and diabetes [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have shown that patients with LTCI are indeed frail. 14 40 41 Sixth, we analysed only three risk scores. Therefore, the incremental value of LTCI over other risk scores was unknown.…”
Section: Study Limitationsmentioning
confidence: 99%